The regulatory effect of saffron stigma on the gene expression of the glucose metabolism key enzymes and stress proteins in streptozotocin-induced diabetic rats - Maryam Motamedrad; Alireza Shokouhifar; Mina Hemmati; Maryam Moossavi (Research in Pharmaceutical Sciences, 2019)
Oxidative stress plays a crucial role in the pathogenesis of hyperglycemia mediated complications. Since a great number of researches have reported antioxidant features of saffron, this study investigated the antioxidant effect of saffron stigma extract (SSE) in streptozotocin-induced diabetic rats. Twenty eight diabetic male Wistar rats were divided in four groups containing: two diabetic groups receiving 25 and 100 mg/kg SSE respectively, one diabetic group receiving glibenclamide (0.6 mg/kg) and one diabetic control group receiving normal saline. Seven healthy adult male Wistar rats were also used as normal control group. After treatment (21 days), fasting blood glucose, insulin, oxidative stress markers, and pancreatic regeneration were assessed. The gene expression level of heat shock factor1, heat shock protein 27, and heat shock protein 70, also glucokinase (GK), and glucose 6-phosphatase (G6Pase) were determined using real-time polymerase chain reaction (RT-PCR). SSE in high dose (100 mg/kg) reduced fasting blood glucose (8.3 ± 0.4 mmol/L) compared with diabetic control (24.6 ± 1.2 mmol/L) (P < 0.05). Furthermore, SSE in high dose increased insulin level compared with diabetic control group (12.7 ± 0.6 vs 7.1 ± 0.3 μϋ/mL). RT-PCR analysis revealed decline in mRNA levels of stress proteins and G6Pase and increase in mRNA level of GK in treatment diabetic groups compared with diabetic control group. Data showed antioxidant and antidiabetic effects of SSE through altering insulin release and glucose metabolism pathways. Hypoglycemic potential of SSE may be due to change in GK and G6Pase enzymes expression. These findings provide a basis for the therapeutic potential of saffron in treatment of diabetes.